2010
DOI: 10.1007/s11102-010-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

A modified protocol using half-dose gadolinium in dynamic 3-Tesla magnetic resonance imaging for detection of ACTH-secreting pituitary tumors

Abstract: A half dose of dynamic resonance imaging contrast material increases the sensitivity of MRI detection of ACTH-secreting pituitary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
1
23
0
2
Order By: Relevance
“…As Fig 3B suggests, an ACTH-secreting microadenoma, in particular, shows contrastenhanced dynamics similar to that of the normal pituitary gland, which seems likely to contribute to failed detection of the lesion on MR imaging. Although the dynamic contrast-enhanced technique is often applied on MR imaging to overcome this issue, scanning time usually required to obtain each dynamic phase ranges from 20 to 30 seconds 6 or is shortened into 12-20 seconds in some cases, but it is not possible to obtain a gapless 3D image as in MCT. Figure 3C, in particular, highlights this problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Fig 3B suggests, an ACTH-secreting microadenoma, in particular, shows contrastenhanced dynamics similar to that of the normal pituitary gland, which seems likely to contribute to failed detection of the lesion on MR imaging. Although the dynamic contrast-enhanced technique is often applied on MR imaging to overcome this issue, scanning time usually required to obtain each dynamic phase ranges from 20 to 30 seconds 6 or is shortened into 12-20 seconds in some cases, but it is not possible to obtain a gapless 3D image as in MCT. Figure 3C, in particular, highlights this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern is the MR image quality of the current study. Previous studies reported exhibiting 66%-100% sensitivity in detecting ACTHsecreting microadenoma 6,7 with the aid of DCE-MR imaging. The sensitivity of the current study for detecting ACTH-secreting microadenomas was as low as 32%, which may suggest that MR images of the current study might have been suboptimized compared with the past literature reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 3-Tesla MRI (130)(131)(132) and other techniques have also been studied. More studies and a greater availability of these methods are needed to confirm their contribution to the diagnosis of CD.…”
Section: Pituitary Mrimentioning
confidence: 99%
“…Furthermore, coronal postcontrast SPGR-MRI images showed to better differentiate microadenoma than conventional SE-MRI imaging protocols of the pituitary gland in patients with suspected Cushing disease [27]. Recently, Portocarrero et al showed that a half-dose gadolinium protocol in dynamic 3-T MRI may further increase the sensitivity of MRI detection of ACTH-secreting pituitary tumors [28]. Nevertheless, false-negative MR results due to microadenomas that are still too small to detect by current imaging are common.…”
Section: Introductionmentioning
confidence: 99%